2018
DOI: 10.1021/acs.jpcc.8b00181
|View full text |Cite
|
Sign up to set email alerts
|

Improved CO2/CH4 Separation Performance in Negatively Charged Nanoporous Graphene Membranes

Abstract: We propose a negatively charged nanoporous graphene (NPG) membrane which presents an improved separation performance of CO2/CH4 gas mixtures. The CO2 permeance and the selectivity of CO2 molecules over CH4 molecules both increase after adding negative partial charges on each carbon atom. The CO2 permeance can increase from 6.81 × 105 GPU for the neutral NPG membrane up to 5.65 × 106 GPU for a partial charge of −0.125 e, and the selectivity increases correspondingly from 10.4 to 42.8. The improved separation pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…Further, they also demonstrated that the ionic liquid thickness and the sizes of anion or pores dictated the CO 2 permeance and selectivity. Similar findings were also reported by Bai's team in their recent report, 54 in which the addition of partial negative charges on carbons enhanced CO 2 affinity over CH 4 .…”
Section: Monolayered Graphene Membranessupporting
confidence: 89%
“…Further, they also demonstrated that the ionic liquid thickness and the sizes of anion or pores dictated the CO 2 permeance and selectivity. Similar findings were also reported by Bai's team in their recent report, 54 in which the addition of partial negative charges on carbons enhanced CO 2 affinity over CH 4 .…”
Section: Monolayered Graphene Membranessupporting
confidence: 89%
“…Molecular dynamics (MD) simulation is an effective method capturing the movements of the atomic particles 30,31 controlled by Newton's laws of motion. 32,33 It can obtain useful information about the moving contact line 34 at the molecular level. Therefore, we present a systematical study of the moving contact line in a waterdecane-silica system from molecular insights by using the MD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Separation of gas mixtures plays an important role in many industrial processes, including the purification of natural gas and landfill gas, oxygen-enriched combustion, hydrogen production, and carbon dioxide sequestration. Significant advantages of the membrane separation system, including no exotic chemicals, a nonmovable structure, high flexibility, and low cost have been confirmed compared to conventional solvent adsorption, cryogenic distillation, and solid adsorption. , In recent years, the development of a two-dimensional (2D) materials family provides many promising membranes for separation, such as pure graphene, functionalized graphene (graphene oxide or fluorine-modified graphene), molybdenum disulfide (MoS 2 ), and hexagonal boron nitride ( h -BN). , …”
mentioning
confidence: 58%